2019
DOI: 10.1177/2045894019895414
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase 7 in diagnosis and differentiation of pulmonary arterial hypertension

Abstract: Pulmonary arterial hypertension is a severe disease for which diagnosis often is delayed. Matrix metalloproteinases have been suggested to play a role in vascular remodeling and pulmonary hypertension development. Our aim was therefore to investigate the potential role of matrix metalloproteinases as biomarkers in diagnosis and differentiation of pulmonary arterial hypertension in relation to various causes of dyspnea and pulmonary hypertension. Using proximity extension assays, 10 matrix metalloproteinases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Numerous studies have investigated the role of matrix degrading proteases and their inhibitors in detail [ 99 ] and the altered expression and activity of MMPs [ 167 ] (MMP-2 [ 221 , 222 ], -7 [ 223 ], -9,-10 [ 5 ], -19 [ 5 ]), ADAMs (ADAM17, ADAM33) [ 5 ], cathepsins (Cath S [ 224 ], Cath L [ 214 ]) and TIMPs (TIMP1 and TIMP3) [ 5 ] has been strongly connected with vascular and ECM remodeling. Several of those enzymes are highly abundant in certain inflammatory cells such as monocytes, macrophages, neutrophils, or mast cells and are often upregulated upon immune cell activation [ 220 ].…”
Section: Bm Components and Their Matrikines In Phmentioning
confidence: 99%
“…Numerous studies have investigated the role of matrix degrading proteases and their inhibitors in detail [ 99 ] and the altered expression and activity of MMPs [ 167 ] (MMP-2 [ 221 , 222 ], -7 [ 223 ], -9,-10 [ 5 ], -19 [ 5 ]), ADAMs (ADAM17, ADAM33) [ 5 ], cathepsins (Cath S [ 224 ], Cath L [ 214 ]) and TIMPs (TIMP1 and TIMP3) [ 5 ] has been strongly connected with vascular and ECM remodeling. Several of those enzymes are highly abundant in certain inflammatory cells such as monocytes, macrophages, neutrophils, or mast cells and are often upregulated upon immune cell activation [ 220 ].…”
Section: Bm Components and Their Matrikines In Phmentioning
confidence: 99%
“…Conceivably, this might suggest a pressure-induced uptake of MMP-7, although its underlying mechanisms and functional consequences remains to be investigated; we have found no accounts in the literature of such pressure-induced MMP-7 uptake. Regardless, increasing evidence implicate MMP-7 in the regulation of vascular tone, tissue remodeling, and the initiation of fibrotic and hypertrophic cascades associated with hypertension (17,(20)(21)(22)(41)(42)(43)(44). In spontaneous hypertensive rats, simultaneous knockdown of MMP-7 and tumor necrosis factor-a-converting enzyme attenuated ANG II-induced hypertension as well as the development of cardiac hypertrophy and fibrosis (17,(20)(21)(22).…”
Section: Acute Pressure Effects On Vasoactive Substancesmentioning
confidence: 99%
“…9 In a recent study, we found that plasma levels of matrix metalloproteinase (MMP)-2, MMP-7, MMP-9, MMP-12, and tissue inhibitor of metalloproteinase-4 were elevated in PAH compared with healthy controls. 11 Plasma levels of MMP-7 were furthermore lower in PAH compared with chronic thrombo-embolic pulmonary hypertension (CTEPH), as well as HF with preserved or reduced ejection fraction (EF), with or without PH. Future studies investigating the relationship between MMP-7 and PAH pathogenesis, pulmonary vascular remodelling, and congestion, as well as its clinical usefulness in differentiation and earlier diagnosis of PAH, were urged for.…”
Section: Introductionmentioning
confidence: 99%
“…Future studies investigating the relationship between MMP-7 and PAH pathogenesis, pulmonary vascular remodelling, and congestion, as well as its clinical usefulness in differentiation and earlier diagnosis of PAH, were urged for. 11 Similarly, proteoglycans have a great influence on ECM development and signalling 12,13 and are known to play an important part in ECM remodelling in heart disease. 14 For instance, decorin interacts with transforming growth factor-β, limiting pulmonary fibrosis, whereas glypican-1 is involved in flow-induced endothelial nitric oxide synthase activation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation